Membangun Jiwa Pebisnis Melalui Kreasi Rumah Honai Di Kalangan Remaja HBM - Cellindion.F.S.Asmuruf; Andini Permatasari; Saoloan Siahaan; Firdosius Nickolaus Malagam; Susana Magdalena Welly Muskita (Jurnal Kewirausahaan Cerdas dan Digital, 2024)
This research discusses the importance of building an entrepreneurial spirit among teenagers, especially by utilizing Rumah Honai creations as an innovative means. Entrepreneurship is seen as a key skill for the younger generation in facing future challenges and contributing to economic growth. Asset-Based Community Development Method (ABCD) is used to identify and utilize community potential and assets in developing empowerment programs. The discussion focuses on two main aspects: building an entrepreneurial spirit and combining innovation, culture and entrepreneurship through Rumah Honai. The development of an entrepreneurial spirit is emphasized as a continuous process that requires commitment, continuous learning and the ability to adapt. The Honai House, as a symbol of Papuan cultural heritage, was introduced as a creative tool to instill entrepreneurial values ​​such as creativity, risk taking and problem solving. This research shows that involving teenagers in the creation of Honai Houses can develop practical business skills, increase cultural awareness, and promote social responsibility. This approach not only builds a strong entrepreneurial foundation but also promotes cultural heritage preservation and sustainable social development. In conclusion, the integration of entrepreneurship with cultural elements such as Rumah Honai offers a holistic approach in preparing the younger generation to face future challenges, while maintaining their cultural identity.